Dari Krinok ke Bungo Krinok: Pemajuan Seni Musik Budaya Melayu Jambi Berkepribadian Menuju Persaingan Global - Mahdi Bahar; Johannes Johannes; Uswan Hasan; Indra Gunawan; Hartati Hartati; Fatonah Fatonah; Zulkarnain Zulkarnain (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2022)
AbstractKrinok is one of the traditional music genres of the people of Jambi, is a treasure of musical culture and has the potential to be advanced. Its musical potential consists of several characters, especially the tone system, melodic contours, grenades, interval patterns, and circular musical journeys, as well as the normative freedom of expression of spontaneous singing texts in the presentation that characterizes this musical entity. In development as an effort to promote, several aspects mandated by the constitution (UUD-1945) are considered, namely, advancing in the midst of world civilization, and through development; (UU-RI) aims as an investment to build the nation's future and civilization, as well as personality. Efforts to advance from Krinok music to Bungo Krinok are manifested in three forms of model music, namely: children, youth and adults. Keywords: Krinok, bungo Krinok, advancement, personality, global